Vector signal processing techniques for all-optical networks - Zhen XING; Hongxiang WANG; Yuefeng JI (Dianxin kexue)
The all-optical vector signal processing technology is of great significance in the evolution of optical network due to its low delay and high efficiency.Therefore,a comprehensive introduction to the technical background and application scheme of the current all-optical signal processing was given.The all-optical signal modulation format was firstly introduced,and the basic characteristics and receiving modes of each modulation format were described.Furthermore,the nonlinear optical effects,which were the basis of all-optical signal processing,were classified and introduced.The occurrence conditions,occurrence process,optical phenomena and common nonlinear media were also illustrated.The advantages of all-optical signal processing technology were briefly introduced and three typical research fields of all-optical signal regeneration,all-optical format conversion and all-optical phase quantization were introduced in detail.Finally,the application prospect of future all-optical vector signal processing technology was prospected.